Exploring Gen-Z's Self-Efficacy and Perceived Urgency of English Proficiency for International Program - Abdurrohman Septiadi; Riskayadi (Edelweiss : Journal Of Innovation In Educational Research, 2026)
This transcendental phenomenological study examines how Generation Z university students in Bangka Belitung, a peripheral Indonesian province, experience English self-efficacy and perceive the urgency of developing proficiency for international mobility programs. While literature often focuses on metropolitan hubs, this study addresses the empirical gap in under-resourced regions by examining self-efficacy and urgency as an interacting pair. Semi-structured interviews were conducted with 12 purposively sampled students, and data were analyzed via Colaizzi’s method. Four themes emerged: English as a "golden ticket" driving urgency; fragile self-efficacy shaped by limited local mastery; vicarious scaffolding from digital environments; and active negotiation between urgency and efficacy. The essence of their lived experience highlights a continuous negotiation between global aspirations and local constraints, managed through self-directed, digital learning. Consequently, the study introduces the model, which extends Bandura's framework by integrating a digital pathway and framing urgency as both a motivational catalyst and a psychological pressure. The findings offer key practical implications for higher education in peripheral regions.